2021
DOI: 10.1021/acsami.1c07680
|View full text |Cite
|
Sign up to set email alerts
|

Tunable and Robust Near-Room-Temperature Intrinsic Ferromagnetism of a van der Waals Layered Cr-Doped 2H-MoTe2 Semiconductor with an Out-of-Plane Anisotropy

Abstract: The intrinsically nonmagnetic feature of van der Waals (vdW) layered transition-metal dichalcogenide (TMDC) semiconductors limits the spintronic applications of these semiconductors. In this paper, we demonstrate a facile Te flux strategy to induce intrinsic ferromagnetism in the vdW layered 2H-MoTe2 semiconductor by magnetic chromium (Cr) doping. The Curie temperature (T c) and saturation magnetization (M s) can be well tuned by adjusting the Cr doping concentration. A notable T c up to 275 K can be achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…20,21 Li et al reported that Fe-doped SnS 2 exhibited ferromagnetic behavior with a Curie temperature (T C ) of 31 K. 22 Chang et al reported that the Cr-doped T d -WTe 2 displayed a maximum saturation magnetization of 4.20 emu g −1 with a T C of 283 K, and the Cr-doped 2H-MoTe 2 displayed a large out-of-plane magnetic anisotropy. 23,24 Nevertheless, the approaches obtaining magnetic-element-doped TMD samples by chemical vapor transport or flux methods followed by mechanical exfoliation still have some inevitable drawbacks including low doping concentration, poor yield, and low scalability. efficient method to obtain magnetic-element-doped TMDs.…”
mentioning
confidence: 99%
“…20,21 Li et al reported that Fe-doped SnS 2 exhibited ferromagnetic behavior with a Curie temperature (T C ) of 31 K. 22 Chang et al reported that the Cr-doped T d -WTe 2 displayed a maximum saturation magnetization of 4.20 emu g −1 with a T C of 283 K, and the Cr-doped 2H-MoTe 2 displayed a large out-of-plane magnetic anisotropy. 23,24 Nevertheless, the approaches obtaining magnetic-element-doped TMD samples by chemical vapor transport or flux methods followed by mechanical exfoliation still have some inevitable drawbacks including low doping concentration, poor yield, and low scalability. efficient method to obtain magnetic-element-doped TMDs.…”
mentioning
confidence: 99%
“…Materials with both ferromagnetic and semiconducting properties are called dilute magnetic semiconductors, which have great potential applications in spintronics and magnetoelectrics. 80,81 The doping of magnetic atoms such as Fe, Co, Ni, Mn, and V will produce ferromagnetism in non-ferromagnetic 2D TMDs. [82][83][84] Thus, the LPI-CVD method has become one of the most effective methods for the controllable synthesis of substitutional magnetic transition metal-doped atomically thin TMDs.…”
Section: Regulation Of the Magnetic Properties Of 2d Tmdsmentioning
confidence: 99%
“…For example, Cr 2 Ge 2 Te 6 , CrI 3 , Fe 3 GaTe 2 , Cr x Ga 1− x Te, Cr–WTe 2 , Cr–MoTe 2 , Cr–NiTe 2 and Ta–MoTe 2 thin flakes exhibit low-temperature or near room temperature layer-dependent ferromagnetism with out-of-plane anisotropy. 3,16–23…”
Section: Introductionsmentioning
confidence: 99%